Markovnikov hydroamination of terminal alkenes by phosphine redox catalysis - Flora Fan; Kassandra F. Sedillo; Alexander J. Maertens; Abigail G. Doyle (Nature, 2026)
Abstract Main-group catalysts that mimic transition metal reactivity can expand substrate tolerance and enable transformations not possible at present with metal catalysis 1 . The discovery that P III and P V phosphorus intermediates can undergo transition-metal-like two-electron chemistry raises the question of whether radical P IV intermediates can mimic other elementary steps in organometallic chemistry 2,3 . Here we describe a phosphine–photoredox catalyst system that promotes intermolecular Markovnikov hydroamination of unactivated terminal alkenes with numerous classes of N–H azoles, a reaction that is not possible with late transition metal catalysis. Experimental and computational mechanistic studies support a new elementary step for main-group catalysis, in which a phosphine radical cation activates the alkene to nucleophilic amination by the azole, a step otherwise associated with transition metals. Given the broad value of nucleophilic alkene functionalization in transition metal catalysis, this P IV mechanism could offer new opportunities for main-group element catalysis and chemical synthesis.